Detecting ocular surface changes associated with soft contact lens wear using conjunctival impression cytology - Swathi Nagarajan; M P Narmada; N Kavitha (Journal of Clinical Ophthalmology and Research, 2018)
Context: Contact lenses (CLs) offer middle ground for those not wishing to wear glasses nor undergo refractive surgeries. These lenses may cause ocular surface changes which cause discomfort on using CLs. Aims: This study aims to evaluate conjunctival cytological changes induced by regular CL use among college students and to determine correlation, if any, between the cytological alteration and symptoms and pattern of CL wear. Settings and Design: This was cross-sectional, observational study. Materials and Methods: Thirty-three students wearing CL and an equal number of age-matched controls were evaluated. Data regarding pattern of CL use were collected. Conjunctival impression cytology (CIC) was performed, appropriately stained, and assessed for cytological changes using the Nelson grading system. Statistical Analysis Used: Odds ratio and Chi-square test to determine the prevalence of conjunctival changes in CL users and those with discomfort. Logistic regression analysis is to determine statistically significant association with alteration in conjunctival cytology. P < 0.05 was considered to be statistically significant. Results: Conjunctival cytological changes were seen exclusively in CL users. The duration of use produced a statistically significant effect on conjunctival cytological changes (P < 0.001). Abnormal conjunctival cytological changes were seen in a majority of symptomatic users (odds ratio: 16.9; P < 0.001). Conclusion: The prevalence of conjunctival cytological alterations is more in symptomatic CL wearers and increases with duration of CL use.